Response outcomes gate the impact of expectations on perceptual decisions - Ainhoa Hermoso-Mendizabal (Nature Portfolio, 2020)
The authors use a combination of perceptual decision making in rats and computational modeling to explore the interplay of priors and sensory cues. They find that rats can learn to either alternate or repeat their actions based on reward likelihood and the influence of bias on their actions disappears after making an error.